Non-Destructive Test and Numerical Approach for Tailrace Safety Evaluation of Ir. H. Djuanda Dam - Damayanti, Vivik Arti; Mulyawati, Fauzia (UKaRsT, 2024)
Dam Ir. H. Djuanda is one of the important infrastructures in managing water resources in Indonesia, with strategic functions such as flood control, irrigation, hydroelectric power plants (PLTA), and raw water supply. The lower channel (tailrace) plays a crucial role in supporting the efficiency of the dam's hydraulic system. However, previous inspections revealed erosion and exposed aggregate in the tailrace concrete layer which could threaten the stability of the structure. This research aims to evaluate the condition of the tailrace structure of Dam Ir. H. Djuanda. An evaluation was carried out by integrating the NDT method using Schmidt Hammer and numerical simulation via Plaxis 2D software. The Schmidt Hammer test data gives an average concrete quality value of 37.47 MPa, while the Plaxis 2D simulation shows that the Cartesian stress ( ,  and ) on the structure is still within safe limits. The simulation results also show a safety factor value of 1.795, which meets the structural safety criteria. These findings indicate that the tailrace concrete was designed with a high safety factor, so that it can withstand hydrostatic loads and ground pressure even though it has been in operation for more than five decades. This research shows that the combination of NDT and numerical simulation is an effective method for evaluating structural conditions without damaging the material. This approach can be adopted to inspect and maintain similar infrastructure to ensure long-term operational stability and sustainability.